Academic Sisterhood: A Collaborative Autoethnography of Two Asian Mothers, Adult Educators, and Scholars - Maria Liu Wong; Aimee Tiu-Wu (Adult Education Research Conference, 2014)
In a global context where Western models and theories continue to dominate and influence adult educational research, multi-vocal perspectives of meaning making and learning from educators raised and educated in the East and West can contribute to more nuanced dialogue and exchange. Utilizing collaborative autoethnography, a qualitative research method that explores society through the lens of self in relation to other (Chang, Ngunjiri & Hernandez, 2013), we provide a window and a mirror into the complexity of East-West learning dynamics as two multicultural Asian immigrant academics educated and raising our children in the West. Together, as mothers, adult educators and emerging scholars, we share our journey of discovery and unpack the influence of our Chinese and Filipino cultural inheritance and North American education. The implications of these stories, and the unique cultural lenses we see through, provide greater insight into the ways of learning, knowing and being at the intersections of our multiple identities.